Perlindungan Hukum Terhadap Merek Dagang di Metaverse Berdasarkan Perspektif Hak Kekayaan Intelektual - Maya Ruhtiani; Yuris Tri Naili; Hesti Ayu Wahyuni (J-LEE - Journal of Law, English, and Economics, 2022)
This article examines violations related to trademarks in the metaverse, which are reviewed from the perspective of intellectual property rights and examines the law enforcement that is applied in the metaverse itself in the event of a trademark violation that is claimed by another person who is not the owner of the rights to the trademark. The type of research used is normative juridical, in which the discussion of this research prioritizes the study of the application of positive legal norms or legal principles applied in Indonesia and approaches through related laws and regulations. The study in this research is an analysis of the first-to-file principle in registering trademarks used in the metaverse and studying the classification of trademarks so that they can be registered in the metaverse so that other people do not use these trademarks. Based on the study in the discussion in this study, it is concluded that the legal protection of trademarks in the metaverse, seen from the perspective of intellectual property rights, still needs to be under the provisions of the applicable laws and regulations. This is marked by the many legal cases against trademark violations in the metaverse itself because trademarks registered in the real world will not automatically be registered in the metaverse unless the rights owner or company registers their trademark through a trademark registration service application on the metaverse.